Periodontal Treatment Protocol for Decompensated Diabetes Patients - Dallaserra, Matías; Morales, Alicia; Hussein, Nayib; Rivera, Marcela; Cavalla, Franco; Baeza, Mauricio; Strauss, Franz J.; Yoma, Yazmin; Suazo, Claudio; Jara, Gisela; Contreras, Johanna; Villanueva, Julio; et al. (Frontiers in Oral Health, 2021)
Background Decompensated diabetes is associated with a higher prevalence and severity of periodontitis and poorer response to periodontal therapy. It is conceivable that periodontal therapy may cause systemic and local complications in this type of patients. The aim of the present study was to identify and describe the best available evidence for the treatment of periodontitis in decompensated diabetics. Material and methods An expert committee including participants from different areas gathered to discuss and develop a treatment guideline under the guidance of the Cochrane Associate Center, Faculty of Dentistry, University of Chile. In total, four research questions were prepared. The questions prepared related to decompensated diabetic patients (glycated hemoglobin >8) were, 1) Does the exposure to periodontal treatment increase the risk of infectious or systemic complications? (2) Does the antibiotic treatment or prophylaxis, compared to not giving it, reduce infectious complications? (3) Does the exposure to periodontal treatment, compared to no treatment, reduce the glycated hemoglobin levels (HbA1c)? Last question was related to diabetic patients, 4) Does the exposure to a higher level of HbA1c, compared to stable levels, increase the risk of infectious complications? Based on these questions, a search strategy was developed using MEDLINE and EPISTEMONIKOS. Only systematic reviews were considered. Results For question 1, the search yielded 12 records in EPISTEMONIKOS and 23 in MEDLINE. None of these studies addressed the question. For question 2, the search yielded 58 records in EPISTEMONIKOS and 11 in MEDLINE. None of these studies addressed the question. For question 3, the search yielded 16 records in EPISTEMONIKOS and 11 in MEDLINE. 13 addressed the question. For question 4, the search yielded 7 records in EPISTEMONIKOS and 9 in MEDLINE. One addressed the question. Conclusions In decompensated diabetic patients, there is lack of scientific information about risk of infectious or systemic complications as a result of periodontal treatment and about the impact of antibiotic treatment or prophylaxis on reduction if infectious complications. A defined HbA1c threshold for dental and periodontal treatment in diabetic patients has yet to be determined. Finally, periodontal treatment does have an impact on HbA1c levels.